Akulturasi Budaya pada Corak Bangsal Mandalasana dalam Objek Wisata Keraton Yogyakarta - MR Santosa, Kaffah Imanuddin; Frisiska, Frisiska; Farrah, Farrah; Indrayanti, Sri; Kusuma Hapsari, Wiranti (Bulletin of Community Engagement, 2024)
There is a separate building that has a contrasting cultural style. Bangsal Mandalasana is a building in the form of a gazebo which functioned as a gathering place for musicians at that time. What is unique is that the styles of musical instruments implemented in this ward are not just traditional Indonesian music, but are musical instruments originating from the West and the Middle East. In fact, some of these instruments are modern musical instruments. It can be seen that there is a common thread between Western culture which has been merged outside the traditional culture of Hinduism, Buddhism and Islam.The aim of this research is to analyze how decorative patterns in cultural acculturation occur in the Mandalasana Ward building. So that we can draw a historical thread of the fusion of western and Javanese culture which became an accentuation of culture within the Ngayogyakarta palace environment.This research uses qualitative methods by producing descriptive data with a study focus on the Yogyakarta Palace tourist attraction by dissecting the cultural acculturation found in Bangsal Mandalasana ornaments.Ward Mandasana has an octagonal shape with an octagonal pillar structure which is also taken from the shape of gazebos in Europe in general. The base is made flat and uses a fence that is integrated with supporting pillars, which is different from other ward shapes in the palace environment. The ornamental style in this ward uses an unusual material, namely stained glass, where stained glass was used in building culture in the West starting in theGothic which was used to decorate the Cathedral windows in the 12th century. The motifs presented are also Western musical instruments which indicate the existence of Western concepts in Bangsal Mandalasana. Keywords: Cultural Acculturation, Bangsal Mandalasana Styles, Cultural Bangsal Mandalasana Styles